Black ovary: Our experience with oophoropexy in all cases of pediatric ovarian torsion and review of relevant literature - R Sriram; M M Zameer; C Vinay; B S Giridhar (Wolters Kluwer Medknow Publications, 2022)
Introduction: Oophorectomy is the treatment of choice in ovarian torsion if after detorsion the ovary looks bluish black. Ovarian preservation is advocated by many studies in the pediatric age group quoting the ability of the ovary to recover despite the appearance after detorsion. Aims: This study aims to review the outcome of salvage surgery (detorsion) in the management of pediatric ovarian torsion. Materials and Methods: This is a retrospective study of girls under 18 years with ovarian torsion treated from January 2016 to June 2021. Data were collated from records and analyzed. Results: Ten girls with ovarian torsion were included (mean age of 11 years). Ultrasonography and Doppler confirmed ovarian torsion in all. Emergency laparoscopy with detorsion was done in all with the mean time lapse from onset to surgery being 35 h. All the ovaries were black initially and persisted to be bluish black after detorsion. All were conserved and fixed to the lateral abdominal wall. In one child with an associated ovarian cyst, the cyst excision was also done. All girls were asymptomatic on follow-up. Ultrasonography at 3-month follow-up showed a normal-sized ovary with good blood flow in 9 out of 10 girls (90% cases). Follicular changes were seen in five girls who had attained puberty. In one girl, the ovary was very small sized and flows were not well visualized. Conclusion: Detorsion and oophoropexy should be the procedure of choice in pediatric patients with ovarian torsion. The gross appearance of the ovary after detorsion should not be the sole determinant for oophorectomy.